Pengaruh Pupuk Organik Cair Berbahan Air Cucian Beras terhadap Pertumbuhan dan Hasil Bayam Hijau (Amaranthus viridis L.) - Chica Nurul Azizah Kadir; Nurul Fajeriana; Muzna Ardin Abdul Gafur; Ismail Munadi Sangadji (Median : Jurnal Ilmu Ilmu Eksakta, 2026)
The productivity of green amaranth (Amaranthus viridis L.) is strongly influenced by nutrient availability during the vegetative growth stage. Meanwhile, rice washing water, a common household waste, contains various organic compounds and essential nutrients, making it a potential raw material for liquid organic fertilizer (LOF). This study aimed to evaluate the effects of different concentrations of fermented rice washing water-based liquid organic fertilizer on the growth and yield of green amaranth and to determine the optimum concentration for enhancing plant productivity. The experiment was conducted from October to December 2024 in a simple greenhouse located in Aimas Unit II, Malasom District, Sorong Regency, Indonesia. A single-factor Completely Randomized Design (CRD) was employed, consisting of four treatments: 0, 50, 75, and 100 mL L⁻¹ of liquid organic fertilizer, with three replications. The fertilizer was applied by soil drenching at a rate of 10 mL per polybag once a week from one to four weeks after transplanting. Observed variables included plant height, number of leaves, and fresh biomass weight. The data were analyzed using analysis of variance (ANOVA), followed by the Honestly Significant Difference (HSD) test at the 5% significance level. The results demonstrated that the application of fermented rice washing water-based liquid organic fertilizer significantly improved the growth and yield of green amaranth. The highest concentration (100 mL L⁻¹) produced the best performance, with a plant height of 50.93 cm, 13.23 leaves per plant, and a fresh biomass weight of 19.63 g plant⁻¹, representing increases of 44.98%, 64.76%, and 130.13%, respectively, compared with the control treatment. These findings indicate that fermented rice washing water-based liquid organic fertilizer has considerable potential as an environmentally friendly alternative fertilizer for improving green amaranth productivity while promoting the sustainable utilization of household organic waste in vegetable production systems.